The new qualification in careers guidance in higher education : a collaborative partnership - Ford, Clare [Verfasser]; Graham, Barbara [Verfasser] (My University, 1994)
Gründung eines Studiengangs in "Career Guidance" in Kooperation des Department of Community Studies an der University of Reading und der Association of Graduate Careers Advisory Services (AGCAS).
Keywords: Berufsberatung; Berufsberater; Ausbildung; Hochschule; Studiengang; Vereinigtes Königreich